O letramento em língua materna e sua relação com a leitura de mundo dos estudantes dos anos iniciais do ensino fundamental - Silva, Flavio Medeiros da (Universidade Federal de São Carlos, 2025)
This paper addresses the importance of literacy in the mother tongue in the early years of elementary school, highlighting its essential role in the formation of critical and conscious individuals. It is based on the premise that teaching and learning processes must be constantly studied and improved, especially in view of current challenges, such as expanding access to school and guaranteeing the right to learning. While literacy is related to the technical mastery of the alphabetic system, literacy involves the social use of written language, with meaning and context, enabling a critical reading of the world. This concept is aligned with the ideas of Freire (1989), who advocates literacy focused on awareness and social transformation. In view of contemporary social changes, it is urgent to redefine such practices, promoting more meaningful learning experiences, focused on the autonomy of students and their ability to critically interpret reality. The purpose of the study is precisely to reflect on how literacy in the mother tongue can contribute to the construction of students' reading of the world in the early years of basic education. To this end, the research adopts a qualitative and bibliographical approach, aligned with the state of the art, based on renowned authors such as Soares (2018), Ferreiro (2017), Freire (1987) and Kleiman (2005). Soares (2018) differentiates literacy from literacy and advocates pedagogical practices that integrate both processes. Ferreiro (2017) emphasizes the constructive nature of literacy, highlighting the different levels of understanding of the writing system. Freire (1987) proposes a critical literacy, based on dialogue and reflection. Kleiman (2005) contributes to the concept of literacy as a social and contextualized practice. The study argues that literacy and literacy should go hand in hand from the early school years, promoting the meaningful appropriation of written language and contributing to the development of students' critical awareness. Literacy, understood as the ability to use written language in different social contexts, is essential for the formation of readers of the world — individuals capable of interpreting, questioning and acting on reality. Thus, the work proposes pedagogical paths that integrate the learning of written language with citizenship formation, valuing the role of the school in the construction of a more just, critical and transformative education.
Literacy in the mother tongue and its relationship with the worldview of students in the early years of elementary school
Keywords: Letramento; Alfabetização; Leitura de mundo; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM